SPOILING CHILDREN AND IMAGES OF GRANDPARENT’S CHILDCARE - Naning Yuliani; I’in Kalimatus Sa’diyah; Asmawati (International Conference on Humanity Education and Society (ICHES), 2026)
Children's behavior is often associated with parenting patterns within the family, which will certainly be highlighted if the child's behavior does not conform to the norms in the family environment. Furthermore, the popular proverb in our society, "the apple doesn't fall far from the tree," further marginalizes parents in relation to negative behavior carried out by children. When this is faced with the condition of incomplete parents and then care is transferred to grandparents. The focus of this study asks how the impact of pampering grandmothers' parenting patterns on children in shaping the character of Generation Z? The purpose of the study was to determine the impact of pampering grandmothers' parenting patterns on shaping the character of Generation Z. This research method is qualitative with a case study approach where data collection was carried out through interviews, observation, and documentation. From the results of the study, one of the factors is parenting patterns. In addition to parenting patterns, it is also known that children's past experiences also support character formation in adolescence.